2015
DOI: 10.1021/pr501312t
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Stress-Induced Metabolic Changes and Altered Male Reproductive Function

Abstract: Heat stress can cause systemic physiological and biochemical alterations in living organisms. In reproductive systems, heat stress induces germ cell loss and poor quality semen. However, until now, little has been known about such a complex regulation process, particularly in the perspective of metabolism. In this study, serum, hypothalamus, and epididymis samples derived from male SD (Sprague-Dawley) rats being exposed to high environmental temperature (40 °C) 2 h per day for 7 consecutive days were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Serum and urine samples above were pretreated according to previously published methods (Hou et al, 2015;Zhang et al, 2016). To minimize systematic analytical deviations, the samples were run in the order of "N group-EE group-P group-14w group" alternately.…”
Section: Sample Pretreatment and Gc/tofms Analysismentioning
confidence: 99%
“…Serum and urine samples above were pretreated according to previously published methods (Hou et al, 2015;Zhang et al, 2016). To minimize systematic analytical deviations, the samples were run in the order of "N group-EE group-P group-14w group" alternately.…”
Section: Sample Pretreatment and Gc/tofms Analysismentioning
confidence: 99%
“…The present study also showed that urea levels were increased in the kisspeptin-10 group compared with the control group. According to previous reports, increased GAAs and urea suggests accelerated of protein disintegration for energy compensation[24]. …”
Section: Discussionmentioning
confidence: 91%
“…Serum samples were first derivatized according to published methods with few modifications and analyzed with GC/TOF-MS[23, 24]. Briefly, the two internal standards (10 μL of 0.3 mg/mL L-2- in water and 10 μL of 1 mg/mL heptadecanoic in acid methanol) were spiked into 200-μL serum samples from each rat in sequence, followed by a 30-s vortex and 10-min storage at -20°C.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that the mechanism of temperature regulation in the male scrotum in high-temperature environments will be damaged, resulting in compromised sperm quality and viability [1]. Some studies have shown that testicular hyperthermia can induce spermatogenic cell apoptosis, affect sperm development, and decrease sperm concentration, resulting in spermatogenic disorder [2]. However, in daily life, more and more men are in high temperatures for short or long periods of time due to their occupations [3] (e.g., sedentary desk workers [4], welders [5], drivers [6], and construction workers [7]).…”
Section: Introductionmentioning
confidence: 99%